Implikatur dalam Talk Show Mata Najwa “KPK Riwayatmu Kini” di Trans 7 Edisi 2021 - Elmawati Jaya; Supriyadi Supriyadi; Herman Didipu (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study’s objectives are (1) descrbing the form of implicature in Mata Najwa’s Talk Show “KPK Riwayatmu Kini” on Trans 7 2021 Edition. (2) characterizing the implicature function in said show. It relied on the descriptive method with qualitative study, while the data collection techniques included listening, reading, and coding techniques. Further, the data were analyzed using data reduction, presentation, and conclusion drawing. The results revealed that the implicature forms in Mata Najwa’s Talk Show “KPK Riwayatmu Kini”, which was re-uploaded on Najwa Shihab’s YouTube channel account, including the form of stating, reporting, showing, mentioning, ordering, begging, demanding, suggesting, challenging, praising, thanking, criticizing, complaining, promising, swearing, threatening, as well as the form of deciding, canceling, forbidding, allowing, and forgiving. Meanwhile, the implicature functions include representative, directive, expressive, commissive, and assertive.